REVISING THE ROLE OF MAGNESIUM IN EPILEPSY RESEARCH AND MANAGEMENT - Stanojević, Marija; Parezanović, Miro; Popović, Aneta; Spasić, Svetolik; Lopičić, Srdjan; Nedeljkov, Vladimir; Jovanović, Zorica; Vučković, Sonja (Srpski medicinski časopis Lekarske komore, 2023)
Magnesium is a bioessential mineral with multiple neuroactive effects. The Mg2+ ion stabilizes excitable membranes. Epilepsy is the third most frequent chronic neurological condition characterized by spontaneous reappearance of unprovoked epileptic seizures, whose underlying mechanisms are not yet completely understood. A literature review of the role of magnesium in basic and clinical epileptology has been performed in order to elucidate the importance of magnesium deficiency in the mechanisms of epileptic brain hyperexcitability, as well as the significance of including magnesium into the management of epilepsy patients. Neuronal magnesium requirements are high. The concentration of magnesium in cerebrospinal fluid (CSF) is even higher than in the blood. In experimental epilepsy research, perfusing hippocampal slices with artificial cerebrospinal fluid containing a low concentration of extracellular Mg2+ ions is a frequently used animal model of spontaneously induced epileptiform activity. Magnesium deficiency is the most frequent clinically unrecognized electrolyte disbalance, often overlooked in epilepsy patients. Serum and CSF Mg2+ concentrations are lower in patients with epilepsy, as compared to healthy controls. Hypomagnesaemia increases seizure frequency and the risk of sudden unexpected death in pharmacoresistant epilepsy. Oral magnesium supplements help achieve better seizure control. Parenterally administered Mg2+ ions efficiently control seizures in certain epileptic encephalopathies, in adults and children (in eclampsia, uremia, porphyria, febrile seizures, infantile spasms), and also helps control status epilepticus. Subclinical magnesium deficiency, which is very frequent in the general population, acts as a factor contributing to seizure generation in epilepsy. It is recommended to assess magnesium status in epilepsy patients. This literature review reveals the therapeutic potential of magnesium as a simple antiepileptic agent, which exceeds its current clinical use.